JALAN TENGAH AL-GHAZALI: SINTESIS AKAL DAN WAHYU SEBAGAI DASAR MODERASI BERAGAMA - Abdulloh; Kholili Hasib; Muhammad Ardiansyah (Journal Multicultural of Islamic Education, 2025)
This article examines Abu Hamid al-Ghazali’s thought on the synthesis between reason (‘aql) and revelation (naql) as a conceptual foundation for religious moderation (wasathiyyah). In the intellectual history of Islam, the tension between philosophical rationalism and traditional textualism has produced a sharp epistemological polarization. Al-Ghazali offers a middle path by positioning reason as an instrument for understanding revelation rather than as an independent authority. Through his major works such as Tahāfut al-Falāsifah, Al-Iqtiṣād fī al-Iʿtiqād, and Iḥyā’ ʿUlūm al-Dīn, he formulates a hierarchical structure of knowledge beginning from sense perception, reason, revelation, to spiritual intuition (kashf) as an integration of rationality, morality, and spirituality. This study employs a library research approach with a descriptive-qualitative analysis of primary and secondary literature related to al-Ghazali’s epistemological framework. The findings reveal that religious moderation in al-Ghazali’s perspective is not a form of compromise but an epistemological and ethical balance between two extremes: rationalism without revelation and literalism without reflection. This synthesis gives rise to a paradigm of religiosity that is critical, contextual, and civilizational. In the contemporary context, al-Ghazali’s thought remains relevant in addressing the challenges of secularism, radicalism, and moral relativism, serving as a foundation for Islamic education and da’wah that foster critical reasoning, spirituality, and tolerance.